2023
DOI: 10.3390/jcm12031150
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Thrombectomy with or without Intravenous Thrombolysis for Anterior Circulation Large Vessel Occlusion in the Imperial College London Thrombectomy Registry

Abstract: Background and purpose. Mechanical thrombectomy (MT) is the standard of care for eligible patients with a large vessel occlusion (LVO) acute ischemic stroke. Among patients undergoing MT there has been uncertainty regarding the role of intravenous thrombolysis (IVT) and previous trials have yielded conflicting results regarding clinical outcomes. We aim to investigate clinical, reperfusion outcomes and safety of MT with or without IVT for ischemic stroke due to anterior circulation LVO. Materials and Methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Intravenous thrombolysis, in addition to mechanical thrombectomy, was associated with better neurological outcome and lower mortality at 3 months. This is consistent with several recent large cohort studies [32‒34], which is debated as a recent meta-analysis concluded to a non-inferiority of thrombectomy alone compared to thrombectomy + thrombolysis [35].…”
Section: Discussionsupporting
confidence: 91%
“…Intravenous thrombolysis, in addition to mechanical thrombectomy, was associated with better neurological outcome and lower mortality at 3 months. This is consistent with several recent large cohort studies [32‒34], which is debated as a recent meta-analysis concluded to a non-inferiority of thrombectomy alone compared to thrombectomy + thrombolysis [35].…”
Section: Discussionsupporting
confidence: 91%
“…The Stroke Department at Charing Cross Hospital is the Northwest London (UK) regional Comprehensive Stroke Centre (CSC) for MT in an urban metropolitan area with more than 6.4 million people. Please refer to our previous manuscripts for the organization of the Imperial Stroke Thrombectomy network [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Stroke Department at Charing Cross Hospital is the Northwest London (UK) regional Comprehensive Stroke Center (CSC) for MT in an urban metropolitan area with more than 6.4 million people. Please refer to our previous manuscripts for the organization of the Imperial Stroke Thrombectomy network [ 14 , 15 ]. In 2019, the life expectancy at birth in London was 85.4 years for women and 81.6 years for men [ 16 ].…”
Section: Methodsmentioning
confidence: 99%